Hillary-hating: And the Politics of Ugly Memes - Blackett, Emma (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
As a politician who became famous for being another politician’s wife, Hillary Clinton has long been a lightning rod for American fears (and hopes) about the state of gender. Although most commentators agree that she has been hated ubiquitously since 1992, scholarship on Hillary-hating almost always considers it a male impulse. This paper asks why right-wing American feminists hate Hillary Clinton. The author studied “Women for Trump” Facebook pages, focusing on memes that present the pro-choice Clinton as a monstrous (anti-)mother. Hatred of Clinton is not produced by ‘reasonable’ public debate, this paper argues; more important are the potent affective charges Clinton’s image carries. A ‘memetic’ analysis is used to look at the affective object-ness of Clinton’s image: where it travels, with what impetus, and what responses it provokes. Affect plays a crucial role in both sharing memes online and the workings of misogyny and racism in right-wing women’s pursuit of the American Dream.